HUBUNGAN GAYA HIDUP DENGAN KEJADIAN BENIGN PROSTATE HYPERPLASIA (Studi Di RSUD Dr. Soedarso Pontianak) - Setyawan, Bagus; Saleh, Ismael; Arfan, Iskandar (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2016)
Benign prostate hyperplasia can lead to increase in size of the prostate that causes interruption of urination. So that can cause infection in the bladder. If the infection occurs then the flow of urine stops, for the diuretic must use a catheter. The incidence of BPH in Hospital Dr. Soedarso increased in 2012, 2013 and 2015. Genesis BPH occurs in lifestyle such as lack of exercise activity, mengkonsusmsi minunam alcohol and smoking behavior.The study aims to know correlation with the incidence of lifestyle Benign Prostate Hyperplasia Study in Hospital Dr. Soedarso Pontianak.This study uses a case design konntrol. The research sample of 62 people (31 cases and 31 controls) were taken with accidendal sampling techniques. The statistical test used chi-square test with 95% confidence level.The results showed that there is significant correlation between smoking habit (p value = 0.025, OR = 3,756, 95% CI = 1138-12391), exercise habits (p value = 0.039, OR = 2,968, 95% CI = 1039-8479. variable unrelated sexual activity (p value = 0.231), alcohol consumption (p value = 0.319). whereas the consumption of vegetables and fruits fiber foods can not be tested because the data are homogeneous.It is advisable to be held health promotion on a regular basis by using waiting room at the clinic Urology by using television media that are already available, and shaping clinical health promotion are about the factors the incidence of BPH for communities to implement prevention of a variety of factors that may cause the occurrence of BPH. Keyword : BPH, smoking, sport